Does Longer Compulsory Education Equalize Schooling by Gender and Rural/Urban Residence? - Kırdar, Murat G.; Dayıoğlu, Meltem; Koç, İsmet (World Bank, Washington, DC, 2015)
This study examines the effects of the extension of compulsory schooling from 5 to 8 years in Turkey in 1997—which involved substantial investment in school infrastructure—on schooling outcomes and, in particular, on the equality of these outcomes between men and women, and urban and rural residents using the Turkish Demographic and Health Surveys. This policy is peculiar because it also changes the sheepskin effects (signaling effects) of schooling, through its redefinition of the schooling tiers. The policy is also interesting due to its large spillover effects on post-compulsory schooling as well as its remarkable overall effect; for instance, we find that the completed years of schooling by age 17 increases by 1.5 years for rural women. The policy equalizes the educational attainment of urban and rural children substantially. The urban-rural gap in the completed years of schooling at age 17 falls by 0.5 years for men and by 0.7 to 0.8 years for women. However, there is no evidence of a narrowing gender gap with the policy. On the contrary, the gender gap in urban areas in post-compulsory schooling widens.